Representation of Government Concerning the Draft of Criminal Code in The Jakarta Post: A Critical Discourse Analysis - Kamelia Sari; Budi Eko Pranoto (Master Program in Linguistics, Diponegoro University, 2021)
This study was purposely done to investigate the representation of the government in The Jakarta Post. Therefore, the research objective of this study is to reveal the representation of the government related to the draft of Criminal Code in The Jakarta Post by using Fairclough three-dimensional model. The three-dimensional model including textual analysis, discourse practice, and social practice were the stages for the researchers to analyze the news. The qualitative descriptive approach was employed by the researchers as the research method. The findings of this current study showed that The Jakarta Post was on the protesters’ side and it negatively represented the government. This research can be a meaningful insight for future researchers who want to conduct a study under a critical discourse analysis theory, for readers to become more aware of reading news, and for journalists to become more aware as well in writing news.